Clinicopathological profile of paroxysmal nocturnal haemoglobinuria clone‐positive aplastic anaemia paediatric patients—A single centre study from North India. (25th June 2018) - Rahman, K.; Mittal, N.; Gupta, R.; Kumar, S.; Gupta, T.; Gupta, A.; Nityanand, S.
Abstract: Introduction: There is a paucity of literature related to the prevalence of Paroxysmal Nocturnal haemoglobinuria (PNH) clones in paediatric aplastic anaemia (AA) patients. Methods: We performed a retrospective analysis over a period of 42 months to study the prevalence of PNH clones in paediatric (age less than 18 years) AA cases, using Fluorescein‐labelled proaerolysin‐based flow cytometric screening and analysed their clinico‐pathological features. Results: PNH clone was identified in 100 (33.2%) of the 301 patients screened. These were comprised of 51 cases of non‐severe AA, 33 cases of severe AA and 16 cases of very severe AA. The median age was 13 years with an M:F ratio of 2.5:1. The median clone size (taken as the proportion of PNH‐positive neutrophils) was 2.15% (range: 0.05%‐93.1%). Although a majority of patients (n = 77) had a clone size of less than 10%, a significant proportion (n = 23) did harbour a clone size of more than 10%. Evidence of haemolysis was observed in 3 patients, all of them having a clone size of more than 10%. Interestingly, 1 patient with dural sinus thrombosis harboured a clone size of 1.25% only. Chromosomal breakage analysis was performed in 61 patients, none of which was positive. Complete and partial response to immunosuppressive therapy was found in 55.1% patients (16/29). Conclusion: There is a high prevalence of PNH clones in paediatric AA patients, which in a majority of cases are of small clone sizes. The use of immunosuppressive therapy does not show a better outcome as compared to PNH‐negative cases.